Test and characterization of reversible solid oxide cells and stacks for innovative renewable energy storage. Issue 5 (11th October 2021) - Hauch, Anne; Ploner, Alexandra; Pylypko, Sergii; Cubizolles, Geraud; Mougin, Julie
Abstract: This work aims at developing a renewable energy storage solution, based on reversible solid oxide cell (rSOC) technology. Firstly, the initially high performing cells were tested as single cells with long‐term reversible SOFC/SOEC load cycles as part of the test sequence. Secondly, similar cells were integrated in a stack design optimized for reversible operation at high degrees of utilization. The long‐term single cell tests showed significant degradation in galvanostatic test periods during electrolysis but not in fuel cell mode prior to starting the reversible load cycling test part. The degradation diminished during the subsequent rSOC operation of the cells operating at 700 °C, +0.6 (SOFC) and −1.2 A cm −2 (SOEC) at fuel utilization up to 80 % in both modes. The long‐term stack tests were conducted applying different switches between SOFC and SOEC modes. Initially, long duration tests (100 h each mode) were performed at pH2 O/pH2 : 50/50 to investigate effect of the polarisation only. The alternating cycle SOEC/SOFC was repeated over 1800 h of testing. Then stack switched daily from SOEC mode (8 h in pH2 O/pH2 : 90/10 at −0.84 A cm −2 ) to SOFC (16 h in H2 at 0.26 A cm −2 ) for 500 h. Stack tests included reversible mode operation for up to several thousands of hours. Abstract : High performing reversible solid oxide cells (rSOC) cells and 5‐cell and 25‐cell stacks are durability tested as solid oxide fuel cells (SOFC), solid oxide electrolysis cells (SOEC) and applying load cycles at 700 °C and current densities of 0.6 A cm −2 (SOFC) and −1.2 A cm −2 . Severe degradation during SOEC operation with declining rate of degradation during load cycling.